2020
DOI: 10.3390/en13051290
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Properties and Usefulness of Ashes from the Corn Grain Drying Process Biomass

Abstract: The paper presents the results of a study on chemical composition of ashes from three types of waste biomass in terms of fertilizer usefulness. Waste from the process of corn grain drying, including corn cobs, corn grains and corn husk and their mixtures in the ratio 4:1 (v/v) were examined. The study proved that corn grain was the material with the highest concentration of macroelements among those studied (P—21,452 ppm, K—25,970 ppm, S—5911 ppm) and the mixture of corn cobs with corn grains (Ca—81,521 ppm). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…It was found that the durability of CG grain waste, and its mixtures with cobs and husks, was much lower compared to other materials and mixtures. The addition of CG reduced the durability of the pellets, which may be due to the chemical composition of this material and its physical properties, as well as mineral impurities, as indicated by other authors [51,54,62]. For further comparison of the obtained results with those of other works, mixtures with an undamaged grain base were considered.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…It was found that the durability of CG grain waste, and its mixtures with cobs and husks, was much lower compared to other materials and mixtures. The addition of CG reduced the durability of the pellets, which may be due to the chemical composition of this material and its physical properties, as well as mineral impurities, as indicated by other authors [51,54,62]. For further comparison of the obtained results with those of other works, mixtures with an undamaged grain base were considered.…”
Section: Resultsmentioning
confidence: 82%
“…In an earlier study, the authors [37] determined the physicochemical properties of residues resulting from the corn drying process, and their mixtures were determined as potential biofuel. In addition, Zaj ąc et al [54] examined the effect of the chemical composition of ash formed from the combustion of waste biomass from the corn grain drying process, analyzed the possibility of its use in fertilization, and estimated the potential risk associated with its introduction into the environment. The aim of the present study was to assess the possibility of managing the waste resulting from the corn grain drying process as a biofuel characterized by low energy consumption in the compaction process and to evaluate the quality of the obtained pellets.…”
Section: Introductionmentioning
confidence: 99%
“…The use of crop residues is undoubtedly an attempt to achieve the effect of a closed cultivation cycle and sustainable development. Hence, the use of anaerobic digestate [31,32] and ashes [33,34] from this type of raw material for fertilizer purposes provides the basis for rational crop and energy management. If the use of agricultural waste as biomass for energy production increases, it could lead to the transformation of previously overlooked residues into a productive socio-economic collaboration between the agriculture and energy sectors [35].…”
Section: Introductionmentioning
confidence: 99%
“…Maj et al (2019) presented the results of chemical compositions and calorific value of husk and cobs cores. Zając et al (2020) tested chemical compositions of corn cobs and husks and based on these results estimated greenhouse gases emissions. Menardo et al (2015) presents the results of carbon and nitrogen content for four morphological parts of corn and the methane yield, but only for varieties FAO class 600.…”
Section: Introductionmentioning
confidence: 99%